Redesign Visual Identity Freesound Band Karya Akhir - Jaka Gagantara; Eliya Pebriyeni (Universitas Katolik Widya Karya Malang, 2023)
This visual identity redesign aims to produce a redesign of the visual identity design that depicts the character of the Freesound band, as well as providing more selling points for the Freesound band apart from the work of the Freesound band's songs. The problems that can be identified are that the visual identity of the Freesound band is not yet optimal, so it is not widely known by the audience and the visual identity of the Freesound band is less attractive, so it has less selling value when applied to supporting media. In solving this problem, the glass box method is used, where this method has several stages, namely starting from the Preparation Stage, Incubation, Illumination, then Verification. This method begins with preparing all the tools and requirements for designing the design, then preparing yourself to process various reference ideas that will be used to design the visual identity design. The results of the redesign of the visual identity design were expressed in the main media, namely the manual book. With the redesign of this visual identity design, it is hoped that it will become something that sells for the Freesound band apart from its songs, such as publishing merchandise or posters for the Freesound band.